The 5th door - Clarke, Greg.; Sietsma, Maggi, 1951-; Valls, Abel.; Neave, Veronica; Expressions Dance Company (Brisbane, Qld. : Expressions Dance Company, 2004)
Based on the ancient story of Blue Beard, a tale of seduction and deceit. A tale told the world over as a cautionary tale against women's "innate wickedness"
Choreographer, Maggi Sietsma; set/costume design, Greg Clarke; drama consultant, Veronica Neave; lighting, Abel Valls
Expressions Dance Company.
DVD format, PAL
Keywords: Modern dance